What is Philosophy? - Tugendhat, Ernst (Analysis. Journal of Philosophical Research, 2018)
Despite all the doubts about the possibility of reaching an agreement around a unitary concept of philosophy, I must now make an attempt to define what we mean by this term. Inevitably, not everyone will agree to such an attempt. The criterion should be here that this concept encompasses as much as possible of how historically it has received that title. What, then, is philosophy?